A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • one year ago

3(5 − 2x) = −2(6 – 3x) − 10x 1. x=38 2.x=-37/38 3.x=-260 4.x=13.5

  • This Question is Closed
  1. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    g Let's solve your equation step-by-step. 3(5−2x)=−2(6−3x)−10x Step 1: Simplify both sides of the equation. 3(5−2x)=−2(6−3x)−10x Simplify: (Show steps) −6x+15=−4x−12 Step 2: Add 4x to both sides. −6x+15+4x=−4x−12+4x −2x+15=−12 Step 3: Subtract 15 from both sides. −2x+15−15=−12−15 −2x=−27 Step 4: Divide both sides by -2. −2x −2 = −27 −2 x= 27 2 Answer: x= 27 2

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...


  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.